Pengaruh pemberian teknik relaksasi Benson terhadap tekanan darah pada penderita hipertensi - Rika Yulendasari; Djunizar Djamaludin (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2021)
Effect of Benson relaxation technique on blood pressure in patients with hypertensionBackground: Hypertension management is classified into non-pharmacological and pharmacological therapy. Non-pharmacological therapy is believed to be safer and has a positive effect. The technique is Benson relaxation, this technique focuses more attention. So it can create a calm environment and can control blood pressure.Purpose: To know effect of Benson's relaxation technique on blood pressure in patients with hypertension at Poncowati Health Center, Central Lampung. Method: Quantitative research with the research design